EFEKTIFITAS DAN KONTRIBUSI PENERIMAAN PBB TERHADAP PENDAPATAN DAERAH KOTA SEMARANG (Students' Journal of Accounting and Banking, 2012)
This study aims to determine the effectiveness of Land and Building Tax Revenue Local Government City of Semarang, to know the rate of revenue growth in the city of Semarang and Local Government to determine the contribution Receipts Tax on income from land and building local government area of Semarang.The population in this study are the data in the PBB Tax Office City of Semarang. With the potential of data samples, the PBB acceptance of Semarang and Semarang revenue. Research data in the form of secondary data obtained from the Central Bureau of Statistics, Office of the DGT, and the PBB KPP Semarang period of time period from 2006 to 2010.From the data obtained it can be concluded that the average city of Semarang on the effectiveness of the PBBited Nations from 2006 to 2010 amoPBBted to 87.17% effective with the criteria. This is caused by the target property tax Semarang city has not been achieved to the fullest. The average value of the rate of growth in Revenue realization of Semarang began in 2006-2010 of 23.42%. The average contribution to the property tax revenue the city of Semarang in years 2006 to 2010 amoPBBted to 14.12% belonging to the category of lessKeywords: Effectiveness of the PBB, The Growth Rate of Revenue and Contribution Revenue Against PBB